IMPROVING GEOGRAPHY PRE-SERVICE TEACHERS’ UNDERSTANDING OF SATELLITE IMAGERY ANALYSIS USING ER MAPPER SOFTWARE WITH A MODULE - Sugandi, Dede; Somantri, Lili (International Journal of Education, 2018)
The development of student potential is influenced by how the teacher prepares the steps of the learning process. This means that teacher’s preparation and planning for the learning process determines the achievement of learning objectives. There is an indication that students have low mastery in the skills of imagery analysis on the topic of remote sensing. This research aims to find ways to assist students in the learning process of remote sensing and find about the appropriateness of the form of learning process to the learning materials as well as the allocated time and the steps in the learning process. More specifically, it aims to assist students in gaining understanding and ability of image data analysis using Er Mapper software. The population consisted of 195 students, while the sample taught to improve their understanding of the steps taken in imagery analysis only included 90 students. The students were divided into two groups, the control class and the experimental class, with 45 students respectively. In assessing students' understanding, this research was aided by four testers who assessed and determined the time taken for students to complete each stage of imagery analysis, with the criteria of: 1) 0-1 (very fast), 2) 1-2 (fast), 3) 2-3 (slow), and 4) 3-4 (very slow). The scores of the imagery analysis of the control class and experimental class students were 3.30 (very good) and 3.38 (very good), respectively, with a difference of 0.08. The difference in the understanding and ability was more strongly indicated by the speed or time taken to complete the analysis stages for each meeting. The control class’ average speed was 3.51 (very slow), while the experimental class was 1.44 (fast). To accelerate the learning process of image analysis, the lab work should be assisted with guidebooks or modules in each meeting. With the module, students can learn independently.